How collective intelligence fosters incremental innovation - Jung-Yong Lee; ChangHyun Jin (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
The study aims to identify motivational factors that lead to collective intelligence and understand how these factors relate to each other and to innovation in enterprises. The study used the convenience sampling of corporate employees who use collective intelligence from corporate panel members (n = 1500). Collective intelligence was found to affect work process, operations, and service innovation. When corporate employees work in an environment where collective intelligence (CI) is highly developed, work procedures or efficiency may differ depending on the onset of CI. This raises the importance of CI within an organization and implies the importance of finding means to vitalize CI. This study provides significant implications for corporations utilizing collective intelligence services, such as online communities. Firstly, such corporations vitalize their services by raising the quality of information and knowledge shared in their workplaces; and secondly, contribution motivations that consider the characteristics of knowledge and information contributors require further development.
Keywords: 650; collective intelligence; incremental innovation; operation; personal contribution motivation; service innovation; social contribution motivation; work process